OPERASI PEMULIHAN SELAPUT DARA BAGI CALON ISTRI DALAM PERSPEKTIF HUKUM ISLAM - Sutriyono Sutriyono; Muhammad Abrori; Adela Idris; Barurotul Amaliyah (SAMAWA, 2024)
This paper aims to determine the view of Islamic law on female hymen surgery. The research methodology used is literature research that relies on a critical and in-depth study of research materials and research results related to the topic. research materials and research results related to the topic of the study, using a juridical and sociological approach. The research methodology used is literature research that relies on a critical and in-depth study of research materials and research results related to the topic of study, using juridical and sociological approaches. The results The results obtained are that contemporary scholars give different opinions. different opinions. There are those who absolutely forbid it for any reason and there are those who allow it with certain conditions. some allow it with certain conditions. The difference of opinion of the scholars scholars on the issue of hymen surgery can be summarized as follows: a) If the hymen is only torn because of sexual intercourse in marriage or adultery that is known to many people, the scholar sexual intercourse in marriage or adultery that is known to many people, the scholars are unanimous in their opinion that it is forbidden. b) If the the hymen is torn because of adultery that is not known to others, rape or other than sexual intercourse, this is where the scholars differ, some allow it on condition that the operation must be performed by a female doctor.